Lecturer, Researcher and Translator in One Person. In Honour of József Goretity's 60th Birthday - Regéczi, Ildikó (Slavica, 2021)
József Goretity has been working at the Institute of Slavonic Studies at the University of Debrecen since 1985 and has been the head of the institute since 2012. During this time he has been teaching courses on 19th and 20th century West-European and Russian literature focusing on the tradition of the novel and mythopoetics at the Department of Comparative Literature as well. In 1996 he was appointed head of the department. Between 1992 and 1999 he was a lecturer at the Faculty of Arts at the University of Miskolc. Besides his teaching activity, József Goretity’s work in the field of literary translation is also outstanding. He has brought such prominent Russian writers to Hungarian-speaking audiences as Narine Abgaryan, Sergey Dovlatov, Viktor Yerofeyev, Viktor Pelevin, Lyudmila Petrushevskaya, Yuri Polyakov, Grigoriy Ryazhskiy, Marina Stepanova, Alexandr Terekhov or Lyudmila Ulickaya. Besides literary texts he also translated literary and cultural studies into Hungarian, such as P. P. Apryshko’s influential monograph The History of Russian Philosophy. József Goretity’s most influential academic works are Idézet paródia és mítosz Fjodor Szologub két regényében and Töredékesség és teljességigény. Huszadik századi orosz prózai művek értelmezése. In 2014 he was awarded the Medal of Pushkin by the President of the Russian Federation. In 2019 he received the prestigous state award, the Golden Cross, for his achievement.